An interactive information exchange in Academic Faculty / Shamsudin Md Sarif, Ahmad Zambri Shahuddin and Nor Azzyati Hashim - Md Sarif, Shamsudin; Shahuddin, Ahmad Zambri; Hashim, Nor Azzyati (2005)
'An Interactive Information Exchange in Academic Faculty' is presented as a preliminary study for developing an interactive information exchange hub at the Faculty of Information Technology & Quantitative Sciences (FTMSK), Universiti Teknologi MARA (UiTM), Shah Alam, Selangor. The first objective of this research is to analyze the interaction pattern of information exchange between and within the student, lecturer and administrative community in FTMSK. Three major communication mediums - Short Messages Services (SMS), web applications and notice boards are identified as important communication mediums that are used for exchanging information in the faculty. In analyzing the interaction pattern of information exchange in the faculty, survey is done with 327 questionnaires are collected. Other than that, interviews are conducted and observations are performed. Results and findings from the surveys are needed to fulfill the second objective of this research. The second objective is to design a framework for an interactive information exchange hub as a platform to facilitate information exchange between communication mediums at the faculty. The framework that is developed is able to provide an interactive information exchange that acts as a hub where all the communities in the faculty can communicate and exchange information between them regardless of what are the types of communication mediums being used by senders and receivers of the message.